Employee engagement: Private sector vs. government sector - Nadia Raihana, Yusof (2015)
Nowadays, employee’s engagement plays a vital role in an organization performance. It is crucial for the employer to know that it is not entirely depends on the employees alone to drive the employee engagement. The whole organizations including the top management must play their part in order to improve the organization’s employee’s engagement. Hence, this study was conducted due to the rising problem of employee engagement especially generation y. The research was conducted in Klang Valley’s Universities. A number of 224 respondents were chosen from the populations. The independent variables that are being used in the research is perceived organization support, rewards and recognition, perceived supervisor support and lastly job characteristics. The results were retrieved by using descriptive analysis, regression analysis, reliability analysis and correlation analysis. For the government sector, the results indicate that there is a significance relationship between independent and dependent variables. However, for the private sector, we found that there is no significance relationship between the independent and dependent variables. Hence the researcher believe that there is another variable that may act as the factor of engagement for private sector